2018
DOI: 10.20944/preprints201805.0217.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Uptake Fluoride from Water by Starch Stabilized Layered Double Hydroxide

Abstract: A novel starch stabilized Mg/Al LDHs material (S-LDH) was prepared in a facile approach and its fluoride ion removal performance was developed. Characterization of S-LDH was employed by using XRD, FTIR and particle size distribution. The adsorption property was studied through the assessment of adsorption isotherms, kinetic models, thermal dynamics and pH influence. The result shows that a low loading of starch of 10 mg onto LDH could obviously improve fluoride removal rate. The S-LDH had 3 times higher adsorp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…A total of 31 out of the 46 included studies reported their cognitive outcomes using mean IQ scores alone. Of these, 25 [22,27,29,30,[32][33][34][35]37,39,[42][43][44][45][47][48][49]51,53,58,[61][62][63][64]67] concluded that the mean IQ levels of children exposed to fluoride at more than or equal to 2 mg/L were significantly lower than those exposed to <2 mg/L, while the remaining 6 studies reported no significant association between the fluoride exposure and the mean IQ of participants [40,41,46,54,65,66].…”
Section: Overall Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 31 out of the 46 included studies reported their cognitive outcomes using mean IQ scores alone. Of these, 25 [22,27,29,30,[32][33][34][35]37,39,[42][43][44][45][47][48][49]51,53,58,[61][62][63][64]67] concluded that the mean IQ levels of children exposed to fluoride at more than or equal to 2 mg/L were significantly lower than those exposed to <2 mg/L, while the remaining 6 studies reported no significant association between the fluoride exposure and the mean IQ of participants [40,41,46,54,65,66].…”
Section: Overall Analysismentioning
confidence: 99%
“…We report results using a subgroup analysis according to (1) study design; (2) age group; (3) fluoride level; and (4) study quality (Table 1). ≥2 mg/L 26 [22,23,25,27,28,30,31,34,37,39,[41][42][43][44][45][46][47][49][50][51]53,56,58,63,64,67] 24 (92) [22,23,25,27,28,30,31,34,37,39,[42][43][44][45]47,[49][50][51]53,56,58,63,64,67] Not reported 9…”
Section: Subgroup Level Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The decline in dental caries accompanied by the rise in the prevalence of fluorosis in communities with both fluoridated and non-fluoridated water have raised public concern about the necessity and efficiency of water fluoridation [18]. Concerns have also been raised about the safety of water fluoridation [19,20]; studies have even related fluoridation with various medical conditions, such as child development impairment [21], an increase in hypothyroidism risk [22], neurotoxicity, and cancer [23,24]. However, adverse effects have been seen with ingestion/water fluoridation doses over the recommended limits.…”
Section: Introductionmentioning
confidence: 99%